19th AIAA/CEAS Aeroacoustics Conference 2013
DOI: 10.2514/6.2013-2190
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolution of Crackle in Jet Noise from High-Performance Engines

Abstract: Crackle, the impulsive quality sometimes present in supersonic jet noise, has traditionally been defined in terms of the pressure waveform skewness. However, recent work has shown that the pressure waveform time derivative is a better quantifier of the acoustic shocks believed to be responsible for its perception. This paper discusses two definitions of crackle, waveform asymmetry versus shock content, and crackle as a source or propagation-related phenomenon. Data from two static military jet aircraft tests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…The authors concluded that skewed waveforms radiate from the shear layer but that the shock content forms during the course of propagation, which could have important implications regarding the perception of jet crackle. 17,18 The ideally and over-expanded laboratory data discussed in this Letter both strengthen and extend these prior conclusions.…”
Section: Introductionsupporting
confidence: 68%
“…The authors concluded that skewed waveforms radiate from the shear layer but that the shock content forms during the course of propagation, which could have important implications regarding the perception of jet crackle. 17,18 The ideally and over-expanded laboratory data discussed in this Letter both strengthen and extend these prior conclusions.…”
Section: Introductionsupporting
confidence: 68%
“…Additionally, the skewness of the pressure derivative has a strong lobe with a maximum that aligns with the peak noise direction, and rapidly decreases at higher angles. Both of these results agree with observations from laboratory measurements by Gee et al [29], Krothapalli et al [30], and Barrs and Tinney [31], in addition to agreeing with the trends observed from full scale measurements [32]. The previously documented significant reductions in OASPL are observed in Fig.…”
Section: Heat Simulated Jetssupporting
confidence: 91%
“…Either the pressure wave develops a sawtooth shape in the course of propagation, or it emerges from a local process with such a waveform. With regard to the former mechanism, Gee et al (2005Gee et al ( , 2008Gee et al ( , 2012Gee et al ( , 2013 conclude that nonlinear propagation is responsible for the discrepancies between observed and linearly predicted propagation pointing to an increase of pressure time-derivative skewness along the Mach wave emission angle in near-field full-scale measurements as evidence of cumulative steepening of the jet noise. With regard to the latter, Fiévet et al (2016) utilize a wave packet approach to show that nonlinear steepening alone is insufficient to produce steepened waveforms in the range-restricted laboratory environment and conclude that the waveforms must be generated by some local mechanism in or near the jet plume.…”
mentioning
confidence: 93%
“…Their original test proposed that the pressure skewness should exceed 0.4 for crackle. More recent work has found the skewness of the pressure time derivative to be a more appropriate indicator (McInerny 1996;Krothapalli, Venkatakrishnan & Lourenco 2000;Gee et al 2007Gee et al , 2013. How the degree of crackle relates to the actual pressure waveform derivative is a perceptual question that remains elusive, but regardless of the test used, the basic criterion for perception of crackle is the presence of sawtooth-like pressure waveforms.…”
mentioning
confidence: 97%